An interactive generative abstraction system for the archetype-based pre-ideation process (IGATY). (10th July 2017) - Suh, Joori
Abstract : Archetype in Greek means an original basis that prevails in all later forms. In the field of design, types and archetypes have been used as analytical tools; unfortunately, they have not been perceived as promising prospects in the search for creative ideas, and the dynamic transformative quality embedded in archetypes has not been fully utilized in the ideation process. This research is an exploration of re-establishing the value of implementing archetypes as generative abstractions in the initial phase of the ideation process. The fundamental structure of archetypes was redefined based on the dual structure of a core signal and a peripheral, and an interactive genetic algorithm (IGA) was implemented to visualize the transformative quality embedded in archetypes. In order to emphasize the experiential property of archetypes, the proposed system was designed to offer users the opportunity to view their exploration in a virtual environment (VE). Emphasis was placed on the artful use of technology in the pre-logical stage of the ideation process based on the theory of archetypes. This paper reports on the results from the experiment based on six museum archetypes focusing on (1) the system's generative quality; (2) the synthesis + evolution function; and (3) VE integration.